RETRACTED: DOES BETTER ENVIRONMENTAL GOVERNANCE REDUCE ANTHROPOGENIC CARBON DIOXIDE EMISSION? A CROSS-COUNTRY ANALYSIS - Krishnan, T. S. (Ecoprint: An International Journal of Ecology, 2016)
The following retraction notice appears in Ecoprint: An International Journal of Ecology Vol.24 (2017) DOI: http://dx.doi.org/10.3126/eco.v24i0.21068 On 11th September 2018 the Editorial Board of Ecoprint: An International Journal of Ecology agreed to retract the article ‘DOES BETTER ENVIRONMENTAL GOVERNANCE REDUCE ANTHROPOGENIC CARBON DIOXIDE EMISSION? A CROSS-COUNTRY ANALYSIS’ published in Ecoprint: An International Journal of Ecology, Vol.23 (2016) pages 29-38 (DOI: http://dx.doi.org/10.3126/eco.v23i0.20649) as it was found to be a duplicate publication of the following article: ‘DOES BETTER ENVIRONMENTAL GOVERNANCE REDUCE ANTHROPOGENIC CARBON DIOXIDE EMISSION? A CROSS-COUNTRY ANALYSIS’ published in Law, Environment and Development Journal 12/1 (2016), p. 35, available at http://www.lead-journal.org/content/16035.pdf